Design of a monitoring and protection system for lithium ion (Li-Ion) batteries on solar panels - Hartono, Hartono; Hidayatulloh, Samsul; Muharni, Yusraini (Universitas Sultan Ageng Tirtayasa, 2024)
Solar energy is one of several new and unlimited renewable energy sources. In Indonesia, sunlight, despite its abundance, is often underutilized as an energy source. It is designed to optimize battery charging and discharging performance while ensuring operational safety through automatic protection. Battery charging tests show that the solar panels can produce a total current of 3.56 Ah in one day, indicating high efficiency under ideal lighting conditions. During the no-load discharge test, the system maintained a stable output voltage between 5.1 and 5.2 V for input voltages between 4 and 12 V, but the output voltage became zero when the input was less than 4 V, indicating the presence of a cut-off mechanism to protect the battery from under-voltage. Further testing with a load showed the battery voltage dropping to 11.26 V, with the current stabilizing at 0.3 A. The protection system is proven to be effective, becoming active at a temperature of 50 degrees Celsius and a current of 1 A, preventing overheating and overcurrent, which can damage the battery or cause a safety hazard.